2017
DOI: 10.1186/s13662-017-1260-9
|View full text |Cite
|
Sign up to set email alerts
|

An efficient scheme for solving a system of fractional differential equations with boundary conditions

Abstract: In this study, the sinc collocation method is used to find an approximate solution of a system of differential equations of fractional order described in the Caputo sense. Some theorems are presented to prove the applicability of the proposed method to the system of fractional order differential equations. Some numerical examples are given to test the performance of the method. Approximate solutions are compared with exact solutions by examples. Some graphs and tables are presented to show the performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Now we have a linear system of with equations given by (9). The unknown coefficients can be determined by solving the system.…”
Section: The Sinc-collocation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now we have a linear system of with equations given by (9). The unknown coefficients can be determined by solving the system.…”
Section: The Sinc-collocation Methodsmentioning
confidence: 99%
“…Since then, fractional calculus developed mainly as a pure theoretical field for mathematicians. However, in the last few decades fractional calculus has fastinated the interest of many researchers in several areas [2][3][4][5][6][7][8][9]. Many mathematicians contributed to the development of fractional calculus, therefore many definitions for the fractional derivative are available In the last years, Khalil et al [10] identified a new definition of fractional derivative called the conformable fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
“…These kinds of systems are usually difficult to solve analytically, especially for singular, nonlinear, and nonhomogenous cases. To this end, extensive research has been carried out to obtain numerical schemes and various methods as utilized in the literature as follows: n [21], the authors applied the Adomian decomposition scheme; in [22], the authors described the sinc collocation algorithm; and in [23] the authors utilized the fractional Lagrangian approach.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are the Caputo derivative, the Riemann-Liouville derivative, Atangana-Baleanu-Caputo derivative, the Caputo-Fabrizio derivative, beta derivative and conformable derivative. Several applications for those derivatives are developed in references [3,4,5,6,7,8,9,10,11,12,13]. In this paper, conformable definition of fractional derivative defined in [14] is considered.…”
Section: Introductionmentioning
confidence: 99%